Mining Anti-Inflammation Molecules From Nippostrongylus brasiliensis-Derived Products Through the Metabolomics Approach - Chen, Yuying; Zhang, Mingming; Ding, Xin; Yang, Yougui; Chen, Yujia; Zhang, Qiang; Fan, Yinwen; Dai, Yang; Wang, Junhong (Frontiers in Cellular and Infection Microbiology, 2021)
Hookworm is one type of soil-transmitted helminth, which could exert an anti-inflammatory effect in human or animal host, which provide a beneficial possibility for discovery of inflammatory-related diseases interventions. Identification of hookworm-derived anti-inflammatory molecules is urgently needed for future translational research. Emergence of metabolomics has become the powerful approach to comprehensively characterize metabolic alterations in recent times. Herein, excretory and secretory products (ESPs) were collected from cultured adult worm, while small intestinal contents were obtained from Nippostrongylus brasiliensis (N. brasiliensis, Nb) infected mice. Through ultra high performance liquid-chromatography coupled with mass spectrometry (UHPLC-MS) platform, metabolomics analysis was used to explore the identification of anti-inflammatory molecules. Out of 45 differential metabolites that were discovered from ESPs, 10 of them showed potential anti-inflammatory properties, which could be subclassed into amino acids, furanocoumarins, linear diarylheptanoids, gamma butyrolactones and alpha-keto acids. In terms of the intestinal contents that were derived from N. brasiliensis-infected mice, 14 out of 301 differential metabolites were discovered to demonstrate anti-inflammatory effects, amidst possible subclass into amino acids, benzylisoquinolines, quaternary ammonium salts, pyrimidines, pregnane steroids, purines, biphenyls and glycerophosphocholines. Furthermore, 9 of the differential metabolites appeared both in ESPs and the infected intestinal contents, wherein 4 were proven to show anti-inflammation properties, namely L-Glutamine, glutamine (Gln), pyruvate and alanine-Gln (Ala-Gln). In summary, we have provided a method for the identification and analysis of parasite derived molecules with potential anti-inflammatory properties in the present study. This array of anti-inflammatory metabolites could provide clues for future evaluation and translational study of these anti-inflammatory molecules.